Super-resolution based image enhancement for magnetic resonance imaging - Chilla, Geetha Soujanya (2017)
Magnetic Resonance Imaging (MRI) is a versatile modality which is widely used for anatomical and physiological imaging in applications including oncology, neuroimaging, and cardiac angiography - to name a few. However, due to patient motion, hardware limitations and constraints on acquisition time, anisotropic images are acquired, sacrificing detail in through-plane. Multiplane super-resolution is a post-processing technique that uses data from multiplane anisotropic acquisition and reconstructs higher resolution MR images. However, certain gaps exist in the application of super-resolution in the context of MRI and research presented in this thesis attempts to address some of the unexplored areas in terms of clinical applications as well as applicability of current state-of-art super-resolution frameworks.